STRATEGI GURU PAI DALAM MENERAPKAN PENDEKATAN KELOMPOK DI SMP MUHAMMADIYAH PAGAR ALAM - Nova Evriani; Yanti Yusipa (STIT Al-Ittihadiyah Labuhanbatu Utara, 2025)
This study aims to analyze the efforts of Islamic Religious Education (PAI) teachers in implementing group-based learning approaches at SMP Muhammadiyah Pagar Alam, as well as to identify supporting and inhibiting factors and their impact on students’ learning engagement. This research employed a qualitative descriptive approach. Data were collected through in-depth interviews, classroom observations, and documentation involving PAI teachers, students, and school administrators. The data were analyzed using an interactive model consisting of data reduction, data display, and conclusion drawing. The findings reveal that PAI teachers apply group learning through discussion groups, collaborative assignments, and small-group guidance. This approach positively influences students’ interaction, learning motivation, and understanding of religious material. However, challenges such as students’ diverse backgrounds, limited facilities, and varying motivation levels remain. The study concludes that group-based learning is effective in PAI instruction when supported by teacher creativity and institutional support.